Fallacies and Lapses in Project Management and the Methods of Reducing Thereof – Selected Aspects - Żarczyńska-Dobiesz, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Existing trends observable in modern economy have made project management become one of the most important solutions applied in the strategy of organization development. Managers are constantly looking for new methods and tools to increase the competitiveness of modern enterprises. The main objective of this article is to identify the areas that are most often neglected during project implementation and identify ways of reducing them. It is also important to draw attention to project manager whose knowledge and skills determine the efficiency and effectiveness of actions taken in this area.